2002
DOI: 10.1021/ja020778f
|View full text |Cite
|
Sign up to set email alerts
|

DNA Interchain Cross-Links Formed by Acrolein and Crotonaldehyde

Abstract: Acrolein and higher alpha,beta-unsaturated aldehydes are bifunctional genotoxins. The deoxyguanosine adduct of acrolein, 3-(2-deoxy-beta-d-erythro-pentofuranosyl)-5,6,7,8-tetrahydro-8-hydroxypyrimido[1,2-a]purin-10(3H)-one (8-hydroxy-1,N(2)-propanodeoxyguanosine, 2a), is a major DNA adduct formed by acrolein. The potential for oligodeoxynucleotide duplexes containing 2a to form interchain cross-links was evaluated by HPLC, CZE, MALDI-TOF, and melting phenomena. Interchain cross-links represent one of the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
251
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 175 publications
(268 citation statements)
references
References 39 publications
15
251
1
1
Order By: Relevance
“…It should be noted that the bypass activity of pol IV was not assessed in the above studies. In contrast, the acrolein-mediated ICLs used in this study are between the exocyclic amino groups of guanine residues in a CpG sequence context (17)(18)(19). This linkage is within the minor groove of DNA, and this difference may strongly dictate which polymerase might be capable of catalyzing TLS past specific ICLs.…”
Section: Discussionmentioning
confidence: 98%
“…It should be noted that the bypass activity of pol IV was not assessed in the above studies. In contrast, the acrolein-mediated ICLs used in this study are between the exocyclic amino groups of guanine residues in a CpG sequence context (17)(18)(19). This linkage is within the minor groove of DNA, and this difference may strongly dictate which polymerase might be capable of catalyzing TLS past specific ICLs.…”
Section: Discussionmentioning
confidence: 98%
“…After >20 days, ~40% cross-link formation occurred for the 6R diastereomer 11 (Figure 10), whereas < 5% cross-link was observed for the 6S diasteromer 12. 55 Digestion of the cross-link yielded the bis-nucleoside pyrimidopurinone, 55 identical to that isolated from acetaldehyde-treated DNA. 19 The presence of the imine linkage was inferred since the cross-link was reductively trapped.…”
Section: Synthesis Of Oligodeoxynucleotides Containing 1n 2 -Dg Enalmentioning
confidence: 94%
“…55,56 A new species formed and reached a level of ~ 50% yield after seven days at 25 °C. Mass spectrometric analysis suggested the chemical nature of the cross-link was a carbinolamine linkage (17), in equilibrium with either or both the imine (18) or pyrimidopurinone (19) forms.…”
Section: Synthesis Of Oligodeoxynucleotides Containing 1n 2 -Dg Enalmentioning
confidence: 99%
“…Recently, a liquid chromatography-electrospray ionization-tandem mass spectrometry method was recently developed [18]. It is reported that the γ-OH-Acr-dG adduct is biologically important in the formation of DNA-DNA, DNA-peptide and DNA-protein cross-links [19], whereas α-OH-Acr-dG does not form these cross-linked species, probably due to its inability to undergo ring-opening [20]. A previous study showed that α-OH-Acr-dG is more mutagenic and genotoxic than γ-OH-Acr-dG [21].…”
Section: Introductionmentioning
confidence: 99%